Gastroduodenal Emphysema with Portal Venous Air due to Congenital Duodenal Web in a Child: A Case Report and Review of Literature - Mihiri Chami Wettasinghe; Shanthini Rosairo; Samantha Kiriwattuduwa; Nuwan Darshana Wickramasinghe (Case Reports in Pediatrics)
Congenital duodenal web causing proximal duodenal obstruction leading to gastroduodenal emphysema is a very rare presentation in infancy. Due to persistent  peristalsis against the duodenal membrane, there is progressive stretching of the duodenal web leading to windsock deformity. We describe a rare case of a child with gastroduodenal emphysema and portal venous air due to duodenal obstruction secondary to a duodenal web. An eighteen-month-old male child, who was under investigation for failure to thrive, presented with a history of persistent projectile vomiting and progressive abdominal distension for two days. The abdominal ultrasound scan revealed air within the portal vein and in the wall of the stomach. Plain X-ray abdomen confirmed the presence of gas in the gastric wall and in the proximal duodenal wall. Upper gastrointestinal contrast study revealed complete obstruction at the second part of the duodenum. The child underwent emergency laparotomy, which revealed a duodenal web as the cause of the duodenal obstruction. During the surgery, windsock deformity was noted. This case illustrates that although rare, proximal duodenal obstruction due to duodenal web may present in early childhood and that alarming imaging features such as gastric emphysema and portal venous air could be associated with benign conditions.